Independent genesis of chimeric TRIM5-cyclophilin proteins in two primate species - Virgen, Cesar A. (National Academy of Sciences, 2008)
The host range of retroviruses is influenced by antiviral proteins such as TRIM5, a restriction factor that recognizes and inactivates incoming retroviral capsids. Remarkably, in Owl monkeys (omk), a cyclophilin A (CypA) cDNA has been transposed into the TRIM5 locus, resulting in the expression of a TRIM5-CypA fusion protein (TRIMCyp) that restricts retroviral infection based on the retroviral capsid-binding specificity of CypA. Here, we report that the seemingly improbable genesis of TRIMCyp has, in fact, occurred twice, and pigtailed macaques (pgt) express an independently generated TRIMCyp protein. The omkTRIMCyp and pgtTRIMCyp proteins restrict infection by several lentiviruses, but their specificities are distinguishable. Surprisingly, pgtTRIMCyp cannot bind to or restrict HIV-1 capsids as a consequence of a point mutation close to the Cyp:capsid-binding interface that was acquired during or after transposition of pgtCypA. However, the same mutation confers on pgtTRIMCyp the ability to restrict FIV in the presence of cyclosporin A, a drug that normally abolishes the interaction between pgtTRIMCyp or omkTRIMCyp and lentiviral capsids. Overall, an intuitively unlikely evolutionary event has, in fact, occurred at least twice in primates and represents a striking example of convergent evolution in divergent species.